2019
DOI: 10.24925/turjaf.v7isp1.167-172.2826
|View full text |Cite
|
Sign up to set email alerts
|

Gıda Patojenlerine Karşı Cardopatium corymbosum L.‘ nin Biyolojik Aktivitelerinin Belirlenmesi

Abstract: Food spoilage pathogens threaten to human health. In this work was studied biological activity of plant known as the “kurtludiken” in Turkey and it is contributed to the literature. Cardopatium corymbosum L. from Mugla region were collected for antimicrobial and antioxidant activity studies. The antimicrobial activity studies were done by disc diffusion method. A total of 8 microorganisms were used at this study, one of them is yeast and the others are bacteria. The 2,2′-azinobis-(3 ethyl benzothiazoline-6-sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, 8 mm inhibition zones were found for S. typhimurium, E. faecalis and Yersinia enterocolitica, 11 mm for Candida albicans (Table 1). Okmen et al (46) reported that cyclamen ethanolic extract was inhibited by 10 mm against E. coli. During the study, Otang and Afolayan (47) detected a 20 mm inhibition zone for S. typhimurium and a 15 mm inhibition zone for E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…However, 8 mm inhibition zones were found for S. typhimurium, E. faecalis and Yersinia enterocolitica, 11 mm for Candida albicans (Table 1). Okmen et al (46) reported that cyclamen ethanolic extract was inhibited by 10 mm against E. coli. During the study, Otang and Afolayan (47) detected a 20 mm inhibition zone for S. typhimurium and a 15 mm inhibition zone for E. coli.…”
Section: Discussionmentioning
confidence: 99%